Effect of Dual‐Site Non‐Invasive Brain Stimulation on Upper‐Limb Function After Stroke: A Systematic Review and Meta‐Analysis - Meng Ren; Jingjing Xu; Wenjing Wang; Lexian Shen; Chaojie Wang; Haoyang Liu; Lu Chen; Chanjing Liu; Yongheng Tang; Jiening Wang; Tiantian Liu (Brain and Behavior)
ABSTRACT Background Non‐invasive brain stimulation (NIBS) has attracted significant attention as it has been proven to be effective in facilitating upper limb motor recovery in patients with stroke. This meta‐analysis evaluates the efficacy of dual‐site non‐invasive brain stimulation (DS‐NIBS) in improving upper extremity motor function after stroke. Methods A PRISMA systematic search was conducted for randomized controlled trials. Two authors independently extracted data, and the quality of included studies was assessed. Results Ten studies were included in the current review. DS‐NIBS demonstrated a significant effect on upper extremity motor function impairment. However, only two studies showed no clear effects of DS‐tDCS on upper extremity motor function after stroke. Due to the limited number of studies, the effects of DS‐NIBS remain inconclusive. Finding This review found evidence for the relatively higher efficacy of DS‐NIBS on post‐stroke upper extremity motor function impairment, compared to the sham and SS‐NIBS. Additionally, DS‐TMS was found to generate better improvement than DS‐tDCS.